Reevaluating the effect of recent immigration on crime: estimating the impact of change in discrete migration flows to the United Kingdom following EU accession - Stansfield, Richard (Crime & delinquency, 2016)
The United Kingdom experienced a rapid inflow of migrants from European Union accession countries between 2004 and 2011, many of whom participated in the Worker Registration Scheme (WRS). Given the relative labor market position of this recent migrant wave, scholars argued that returns to criminal activity were negligible. Yet, recent data from London’s Metropolitan Police estimated that foreign-born nationals from Poland, Lithuania, and other Eastern European nations were responsible for almost 25% of alleged crimes in London between 2010 and 2011. With the United Kingdom set to see an influx of Romanian and Bulgarian immigrants starting in 2014, political and public arenas became rife with fears of a growing Eastern European crime wave. This article attempted to bring some coherence to the relationship between recent Eastern European immigration and multiple forms of crime in the United Kingdom. Using data from 348 local authorities in England and Wales, this study examined recent immigration composition effects on crime. The study also went beyond existing studies on immigration and crime by examining the effects of change in employment-related migration flows, study-related migration, and other migration flows since 2004. Results confirmed that areas that saw the highest rates of immigration do not have higher rates of violence. These areas did exhibit higher rates of drug offenses, however, that could not be explained away by differences in structural conditions. Finally, evidence was found that the reason for migration was critical in predicting criminal returns.